Understanding Customer Satisfaction: A Study of Convenience Stores - Jaafri, Nur Ain Hanisah; Mansor, Aida Azlina (Information Management and Business Review, 2024)
This study explores the impact of customer satisfaction on purchasing behavior within convenience stores, focusing on four key determinants: service quality, perceived value, product quality, and trust, perceived value, and trust. The growing population and increasing consumer demand have prompted companies to enhance productivity and service standards across their convenience store branches. To maintain competitiveness and attract a diverse customer base—comprising existing, new, and potential customers—businesses need to review and refine their operational strategies continuously. The study’s methodology involved a structured approach to gathering quantitative data from a specific sample of convenience store customers in Bentong City. By using surveys and questionnaires, the research aimed to capture relevant information directly from the consumers, providing insights into their experiences and satisfaction with the convenience stores. The non-probability convenience sampling method facilitated the collection of data from readily available participants, ensuring a practical and timely data collection process. Using a data set collected from 220 respondents who utilized products and services at a convenience store, this research aims to empirically investigate the relationships between service quality, perceived value, product quality, and trust, perceived value, trust, and overall customer satisfaction. The findings indicate that while all four factors contribute to customer satisfaction, service quality, perceived value, and trust exert a significantly stronger influence compared to product quality. These insights underscore the importance of prioritizing service enhancement, value creation, and trust-building initiatives in the strategic management of convenience stores, thereby ensuring sustained customer satisfaction and loyalty.